2019
DOI: 10.14207/ejsd.2019.v8n4p176
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Environmental and Economic Performance of Remote Communities

Abstract: Remote communities such as oil production sites, post-disaster housing camps, and military forwardoperating bases (FOB) are often detached from established infrastructure grids, requiring a constantresupply of resources. In one instance, a 600-person FOB required 22 trucks per day to delivernecessary fuel and water and remove generated wastes. This logistical burden produces negativeenvironmental impacts and increases operational costs. To minimize these consequences,construction planners can implement sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…By quantifying the logistical impact of equipment and the volume of fuel, water, and waste transported on-and off-site each day, the work identified infrastructure alternatives that improved personnel safety and minimized transportation expenses. Filer and Schuldt [25] expanded Putnam's approach to quantify the impact of an infrastructure alternative's resource consumption and logistics on the environment. While the authors computed GHG emissions and total cost for various infrastructure systems, they failed to fully consider the impact of transportation requirements or establish optimal tradeoffs between competing objectives.…”
Section: Introductionmentioning
confidence: 99%
“…By quantifying the logistical impact of equipment and the volume of fuel, water, and waste transported on-and off-site each day, the work identified infrastructure alternatives that improved personnel safety and minimized transportation expenses. Filer and Schuldt [25] expanded Putnam's approach to quantify the impact of an infrastructure alternative's resource consumption and logistics on the environment. While the authors computed GHG emissions and total cost for various infrastructure systems, they failed to fully consider the impact of transportation requirements or establish optimal tradeoffs between competing objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Connecting a solar array to an energy-storage system allows excess energy produced during peak hours to be captured and discharged during periods of darkness, further reducing the fuel consumed by the generator [10]. Several military studies have also demonstrated the feasibility of connecting photovoltaic (PV) panels to soft-walled shelters to reduce the overall power demand [4,[11][12][13][14][15]. Additionally, tents with integrated PV cells have proven effective in meeting the electricity needs of a displaced refugee population [16,17].…”
Section: Introductionmentioning
confidence: 99%